A Comparison of Selected Maldives and Dried Fish Processing and Handling Practices among Different Processors in Southern Sri Lanka - Wickrama, P.S.S.L.; Sandika, A.L.; Harshana, P.V.S. (University of Jaffna, 2021)
Dried and Maldives fish plays an essential role in human nutrition by providing animal proteins, healthy fats and a unique source of other essential nutrients. Nutritional components and sensory properties of dried fish are influenced by processing and handling practices. Nowadays, it is considered that the dried fishes available in the market are in poor quality due to bacterial and fungal contamination, elevated levels of histamine and low protein and mineral contents. Therefore, this study seeks to compare the nature of selected processing and handling practices of dried and Maldives fish in order to ensure the good manufacturing practices towards better product. The snowball sampling technique was used to select 25 participants, including 10 Maldives fish processors and 15 dried fish processors in Southern Sri Lanka. In-depth interviews were employed to collect primary data and secondary data were collected from reputed published materials. Data were analyzed using descriptive statistical methods. All dried and Maldives fish processors use poor grade large pelagic raw fish species, while 88% of processors use eroded and dirty equipment during their processing. It is reported that 88% of processors use sea water and 12% use fresh water to wash raw fish. Another 40% of fish processors of Maldives fish use curry leaves and gummy-gutta during the boiling and smoking steps to improve taste and smell. Seventy-six percentage of dried fish processors sun dry their products an average of three days and 72% of Maldives fish processors dry the fish for an average of 10 days, while others take less duration for drying during the best sunny season. All Maldives fish and 30% of dried fish processors use drying racks to dry their products, while others lie on mats and tents. About 20% of processors sort their products to separate animal excrement and other contaminations. The 50% of processors grade their products based on appearance, size and texture. In conclusion, processors pay very little attention to the quality of the processing and handling practices. Therefore, appropriate management mechanisms and attention should be put in place to improve the end product quality through the exchange of knowledge between processors.
Keywords: Dried fish; Maldives fish; Processing methods; Quality product